Perceptions of Organizational Politics Impact on Information Systems Success: An Empirical Investigation of Banking Sector - Romi, Ismail (Archives of Business Research, 2022)
The Extent of information systems success is based on various determinants, including perceptions of organizational politics. This paper aims to determine the impact of perceptions of organizational politics on information systems success in banks. A comprehensive model was developed, and data were collected from information systems users in banks. This study used correlation matrix, descriptive analysis and regression analysis to analyze data, and test the suggested hypotheses. The results revealed that banks information systems users have a lower “general political behavior”. In addition to moderate responses to “getting along to get ahead”, and “pay and promotion” political perspectives. Furthermore, getting along to get ahead and pay and promotion political perspectives are positively impacting system quality, information quality, and service quality of the information systems dimensions. These findings indicated that the more existence of group loyalties, and more employee fit for the bank will lead to more success of information systems. Furthermore, a lot of work is required to enhance information systems success, mainly; IS users’ feelings towards all information systems success dimensions by encouraging employees’ good ideas, teamwork, honesty, and make their minds for the benefit of information system.